Pengembangan Tata Kelola Destinasi Pariwisata Melalui Pendekatan Pemberdayaan Masyarakat di Kampung Wisata Braga - Asy'ari, Rifqi; Afriza, Lia; Silalahi, Agnes Tresia (Yayasan Literasi Sains Indonesia, 2022)
The Bandung City Government has launched creative villages in 30 sub-districts in Bandung City. The tourism development that is in the management of tourist village destinations in Bandung City can be formed as a thematic tourism village with important attributes that integrate the tourism potential that exists in the tourist village. One of them is the Tourism Village which is carried out in development, namely the Braga Tourism Village through a community empowerment approach. Kampung Wisata Braga is the focus of tourism development in the form of community empowerment carried out by the Bandung City Culture and Tourism Office to be steps taken in preparing the management of tourism destinations in Bandung City in 2020 through special allocation funds. This study aims to identify the tourist attractions in the Braga Tourism Village which is integrated in the Braga Village with a community empowerment approach. The method used is a survey method with a qualitative approach through community empowerment techniques. Obstacles that occur from destination management in Bandung City, especially those that occur in Kampung Wisata Braga, from the results of research, namely management, facilities and regulations are obstacles that occur in development. The results of the development of tourism destination governance that can be developed in the Braga Tourism Village by integrating the tourism potential in Braga Village in the form of the main activities that exist, namely traveling around visiting cultural heritage and getting to know history.